Застосування методу R-функцій до моделювання нестаціонарних течій в’язкої теплопровідної рідини (лінеарізована задача) - Курлов, Є. Е. (ХНУРЕ, 2021)
The linear problem of calculating the non-stationary flat-parallel flow of a viscous heat-conductive non-contiguous liquid is considered. For its numerical solution, it is proposed to use the R-function method and the Galerkin method for non-stationary problems.
Keywords: нестаціонарна плоско-паралельна течія; в’язка теплопровідна нестислива рідина; початково-крайова задача; метод Гальоркіна; метод R-функцій